Perangkat Digital dan Kapital Simbolik: Pembentukan Identitas dan Eksklusi Sosial di Kalangan Remaja Kota dan Pinggiran di Ambon - Yanwarin, Boy; Rahawarin, Yunus (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article examines how digital devices, particularly gadgets, function as symbolic capital in the formation of social identity and digital exclusion among adolescents in Ambon City, Indonesia. The study focuses on two areas with distinct social and geographical characteristics: Batu Merah (urban) and Laha (peripheral). The research aims to analyze the social meanings attached to gadget ownership, investigate the impact of unequal technological access on social exclusion, and explore how gadgets operate as markers of social status among youth. Employing a qualitative approach through phenomenology and mini-ethnography, data were collected via in-depth interviews, participant observation, and focus group discussions. Thematic analysis was conducted using Pierre Bourdieu’s theoretical framework of symbolic capital, habitus, and social distinction. Findings reveal that among Ambonese youth, gadgets serve not only as communication tools but also as indicators of emerging social class. Urban adolescents tend to have greater access to advanced devices and faster internet, reinforcing their dominance in digital interactions, while those in peripheral areas face symbolic and practical exclusion. This study contributes to localized digital sociology by offering a contextual analysis of urban–rural dynamics in Ambon's social structure and highlights the need for social science and humanities research to critically address technological inequalities in Eastern Indonesia.